2018
DOI: 10.1155/2018/6595643
|View full text |Cite
|
Sign up to set email alerts
|

The Bone Black Pigment Identification by Noninvasive, In Situ Infrared Reflection Spectroscopy

Abstract: Two real case studies, an oil painting on woven paper and a cycle of mural paintings, have been presented to validate the use of infrared reflection spectroscopy as suitable technique for the identification of bone black pigment. By the use of the sharp weak band at 2013 cm−1, it has been possible to distinguish animal carbon-based blacks by a noninvasive method. Finally, an attempt for an eventual assignment for the widely used sharp band at 2013 cm−1 is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
1
19
1
Order By: Relevance
“…These white pigments are probably used either as pigments in lightening the color tones or as components forming the white ground layer. Quartz (SiO 2 ) in the ground layer is probably an impurity [50,51]. The results of FTIR also confirm the most used materials detected by MA-XRF and EDX.…”
Section: Discussionsupporting
confidence: 67%
“…These white pigments are probably used either as pigments in lightening the color tones or as components forming the white ground layer. Quartz (SiO 2 ) in the ground layer is probably an impurity [50,51]. The results of FTIR also confirm the most used materials detected by MA-XRF and EDX.…”
Section: Discussionsupporting
confidence: 67%
“…1038 and 604 cm −1 and marker signal at ca. 2010 cm −1 [50], Figure S4) as a pigment and of a lipid-based medium (CH stretching bands at ca. 2916 and 2842 cm −1 and carbonyl band at ca.…”
Section: Superficie 207mentioning
confidence: 99%
“…1038 ν 3 (PO 4 3− ), 604 and 567 ν 4 (PO 4 3− ) and the signal at ca. 2010 cm −1 indicated that the black pigment was ivory black [50], probably mixed with Prussian blue, which was evident from the weak CN stretching band at ca. 2097 cm −1 [57].…”
Section: Superficie 553mentioning
confidence: 99%
“…The Raman spectrum recorded on the black pigment ] group is observed at 980 cm −1 . 35,36 Lampblack, charcoal black and bone-ivory black were common forms of carbon black in ancient Egypt. 37 Few exceptions were found in the application of magnetite (Fe 3 O 4 ) and pyrolusite (MnO 2 ).…”
Section: Black Pigmentmentioning
confidence: 99%